Community-based health insurance and healthcare service utilisation, North-West, Ethiopia: a comparative, cross-sectional study - Atnafu, Desta Debalkie (BMJ Open, 2018)
OBJECTIVES: The objective of this study was to compare differences in healthcare utilisation between community-based health insurance member households and non-member households and to identify factors for community-based health insurance enrolment in South Achefer District. DESIGN: Comparative, cross-sectional study. SETTINGS: Community-based. PARTICIPANTS: A total of 652 selected households (326 insured and 326 uninsured households) participated in the study. METHODS: A two-sample t-test (for proportions) and χ(2) (for categorical data) were computed. MAIN OUTCOME MEASURE: Utilisation of healthcare. RESULTS: There was a significant difference in the rate of healthcare utilisation between insured (50.5%) and uninsured (29.3%) households (χ(2)=27.864, p<0.001). Significant variations of enrolment status in community-based health insurance were observed in the following variables: educational status, family size, occupation, marital status, travel time to the nearest health institution, perceived quality of care, first choice of place for treatment during illness and expected healthcare cost of a recent treatment. CONCLUSIONS: Utilisation of health services among insured households with community-based health insurance was higher. Educational status, family size, occupation, marital status, travel time to the nearest health institution, perceived quality of care, first choice of place for treatment during illness and expected healthcare cost of a recent treatment should be emphasised to enhance community health insurance enrolment.